Processing and characterization of honey glazed herbed anchovies (Stolephorus sp.). - Jamison, Keziah Lasalita (2017.)
Anchovies (Stolephorus sp.), locally called ?dilis?, is an abundant coastal pelagic fish known for its high content of protein, minerals, and functional fatty acids like docosahexanoic acid (DHA) and eicosapentanoic acid (EPA). Enhancement of delectability, stability, and acceptability of anchovies by re-processing of re-processing of pre-dried salted anchovies into flavored form was the main purpose of this study. Three time-temperature combinations of drying were tested on marinated pre-dried salted anchovies to produce honey glazed herbed anchovies (HGA) using Completely Ramdomized Design (CRD) with two replications. The most preferred treatment of HGA was obtained by drying at 60°C for 7 hours in a cabinet dryer. Mann-Whitney at P0.05 indicated significantly lower values of moisture content (8.36%), crude protein (41.35%), salt content as NaCl (2.18%), and water activity (0.51) of the most preferred HGA than the Control. Microbiological assessment by Total Plate Count (TPC) showed lower microbial load in the most preferred HGA (1.7 x 105), but the difference between them was not significant. The process of marinating, glazing with honey, and re-drying may have made the pre-dried salted anchovies drier and more stable than its previous form. However, re-drying may be a factor in the degradation and lowering of protein in the product. Marinating could have leached-out the salt, thus reducing the salt content of the final product. The most preferred HGA was described by a panel of 50 evaluators as very crispy with slightly bitter taste, moderately distinct anchovy flavor, and color of 10YR 5/8 based on the Munsell colors. The perception of bitterness did not reduce the product?s acceptability, rated as ?like very much?. The characteristics of the product conform to the parameters set by the Philippine National Standards for Dried Anchovies.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Anchovies; Stolephorus sp